Analysis of Current Ratio and Debt Ratio on Profitability of Retail Trade Sub-Sector Companies Listed on the Indonesian Stock Exchange for the Period 2018-2022 - Wahyu Indah Mursalini; Rasidah Nasrah; Suci Yoga Anggriani (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
The main objective of this study is to investigate how the current ratio and debt ratio influence the profitability of retail trade sub-sector firms that are publicly listed on the Indonesian stock exchange from 2018 to 2022. The research utilises quantitative methods and correlation research, with a sample size of 22 companies and 110 annual financial reports. The data gathering process involves purposive sampling, while the analysis includes descriptive tests, classical assumption tests, multiple linear regression analysis, coefficient of determination (R²), and hypothesis testing. According to the research findings, it is indicated that the current ratio has a certain impact on profitability with a significance value of 0.002<0.05. Additionally, the debt ratio has a partial effect on profitability with a significance value of 0.000<0.05. At the same time, both the current ratio and debt ratio collectively affect profitability with an f value of 19.271>3.12 and a significance value of 0.000. The combined influence of the current ratio and debt ratio on profitability is estimated to be 34.9%.